Agriculture and social protection: The experience of Ethiopia’s Productive Safety Net Program - Tadesse, Getaw (International Food Policy Research Institute, 2018)
In this chapter, critical lessons and insights regarding the effects of social protection on agriculture are drawn from an assessment of the benefits and challenges of linking social protection with agriculture using the experiences of and empirical findings from the Ethiopian Productive Safety Net Program (PSNP)—the second-largest social protection program in Africa.